A unique case of classic pleomorphic sarcoma restricted to the toes - Siddiqui, Abdul Rehman; Akbar, Suha Mohammed (International Surgery Journal, 2021)
Over 50% of soft tissue sarcomas occurring in older adults are histologically pleomorphic and high grade. Most have traditionally been classified as malignant fibrous histiocytoma (MFH). MFH was originally defined as a malignant pleomorphic spindle cell neoplasm showing fibroblastic and histiocytic differentiation. More recently, pathologists have accepted that this morphology may be shared by a wide range of malignant neoplasms. Many sarcomas that were previously classified as pleomorphic MFH, on careful immunohistochemical and histopathologic analyses, revealed a specific line of differentiation and could be reclassified as myxofibrosarcoma (30%), myogenic sarcoma (30%), liposarcoma (4%), malignant peripheral nerve sheath tumor (2%), or soft tissue osteosarcoma (3%), whereas about 30% had no specific line of differentiation or were myofibroblastic. The term undifferentiated pleomorphic sarcoma (UPS) is now reserved for pleomorphic sarcomas that show no definable line of differentiation by current technology. The majority of extremity sarcomas occur in the lower extremity (74 vs. 26% in the upper limb). According to one of the studies conducted on 315 patients, non-metastatic soft tissue sarcoma of the lower extremity who were treated at one institution over a ten-year period. Sixty-six percent of the lesions were above the knee, and 60% were high grade. This case had a 3x3 cm ulcer at the 3rd toe in a 30-year-old male patient who subsequently underwent midfoot ampuatation.